2007
DOI: 10.1074/jbc.m704476200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Blasticidin S Deaminase (BSD)

Abstract: The set of blasticidin S (BS) and blasticidin S deaminase (BSD) is a widely used selectable marker for gene transfer experiments. BSD is a member of the cytidine deaminase (CDA) family; it is a zinc-dependent enzyme with three cysteines and one water molecule as zinc ligands. The crystal structures of BSD were determined in six states (i.e. native, substrate-bound, product-bound, cacodylate-bound, substrate-bound E56Q mutant, and R90K mutant). In the structures, the zinc position and coordination structures va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…The X-ray structure revealed a novel, extended V-shaped homotetramer, contrasting earlier findings for other deaminases that exhibited square/rectangular homodimeric or homotetrameric assemblies with the Zn coordinated active-sites of all subunits at the center (30-32). Since little was known about the function of A2, rendering structure-function studies unfeasible, the major value of the A2 structure was its utility as a surrogate for other APOBEC/AID family members.…”
contrasting
confidence: 99%
“…The X-ray structure revealed a novel, extended V-shaped homotetramer, contrasting earlier findings for other deaminases that exhibited square/rectangular homodimeric or homotetrameric assemblies with the Zn coordinated active-sites of all subunits at the center (30-32). Since little was known about the function of A2, rendering structure-function studies unfeasible, the major value of the A2 structure was its utility as a surrogate for other APOBEC/AID family members.…”
contrasting
confidence: 99%
“…All previous data of APOBEC crystal and NMR structures [9, 10, 1222, 34, 35], as well as structures of phylogenetically related enzymes (CD, CDD1, ADAR, ADAT [3651]), indicate zinc coordination at the active site.. For all tested enzymes, mutagenesis studies have shown that the conserved zinc coordinating residues are essential for catalytic activity ( e.g ., A3F H249, E251, C280, and C283 [46]). However, the active site glutamic acid may be dispensable for zinc binding because changing this residue in A3A (E72A) or in the distantly related Blasticidin S. deaminase (E56Q) did not prevent the protein from coordinating zinc as evidenced by crystal structures [9, 52]. Our structural and biochemical data indicate that zinc binding in the A3F catalytic domain is mainly influenced by ionic conditions and the redox state of the catalytic histidine and cysteine residues.…”
Section: Discussionmentioning
confidence: 76%
“…This observation has been drawn upon the analysis of all the sites included in the superfamilies of these Zn-sites, which represent all the available structural information on the various coordination states accessible to zinc in these enzymes. Out of 261 structures inspected, only two structures of blasticidin S deaminase (PDB codes 1wn6 and 2z3i, the latter being a single mutant of the former), which have been determined within the same study, show a five-coordinate zinc, which would occur in a putative reaction intermediate [34]. Indeed, this observation still holds when all the catalytic sites in our dataset (i.e., a total of 4524 sites in 2404 PDB structures) are taken into account.…”
Section: Resultsmentioning
confidence: 99%